Education On Food Poisoning For Internal Medicine Outpatients At Rsu Haji Surabaya - Gunawan Widodo; Yulia Merita Putri; Dewi Ritna Ningrum; Selva Dhea Andini; Aisha Putri Maharani; Ahmad Kahfi Daary; Nauval Halim (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2025)
Background: The World Health Organization (WHO) reports that 1 in 10 people worldwide suffers from illnesses caused by contaminated food, resulting in approximately two million deaths annually, particularly in developing countries. Food poisoning, caused by bacteria, viruses, parasites, or toxins, primarily affects children. Consumption of contaminated food can lead to symptoms such as diarrhea, fever, and nausea. The link between food and health has been recognized since the time of Hippocrates. The occurrence of this disease is influenced by factors like food production, handling, and hygiene. Prevention can be achieved through proper food management and hygienic practices. To raise awareness of food poisoning, the B39 group of medical interns proposed an educational program in the Internal Medicine Outpatient Clinic at RSU Haji, East Java Province. The objective of this service initiative is to increase awareness among patients and families in the Internal Medicine Clinic at RSU Haji Surabaya on the importance of preventing food poisoning following the educational session. Methods: This study uses a descriptive method with a cross-sectional design, conducted in the Internal Medicine Clinic at RSU Haji Surabaya on August 18, 2023. The study population includes all patients present, with a sample of 17 individuals who completed a questionnaire. Inclusion criteria include patients willing to participate, while exclusion criteria are patients unable to read or write. The sampling technique used is total sampling. The independent variable is the patient's understanding of food poisoning, while the dependent variable is the knowledge and food safety practices after the education session. Data collection was carried out using a questionnaire that has been validated and tested for reliability, consisting of 15 questions on a Guttman scale. Data were analyzed based on questionnaire responses to assess patients' understanding of food poisoning. Results: The pre-test results showed that most patients had minimal knowledge of food poisoning, with 8 patients scoring <60, 6 patients scoring between 60-79, and 3 patients scoring >80. After the educational material was delivered, a post-test was conducted to evaluate patient understanding. Post-test results showed 6 patients scoring >80, 8 patients scoring between 60-79, and 3 patients scoring <60. A total of 14 out of 17 patients (82%) achieved scores above 60. Therefore, the target for raising awareness about food poisoning was achieved. Conclusion: Food poisoning is caused by contaminated food due to bacteria or parasites, with symptoms such as nausea, vomiting, and diarrhea. Management includes assessing consciousness, analyzing suspected food, and preventing dehydration. Severe symptoms require medical treatment. Preventive measures include maintaining hygiene, washing food ingredients, and cooking thoroughly.